The Role of Individual Ethics and Organizational Culture in Maximizing Company Profitability - Dedy Harianto Hutasoit; Gadis Amelia Pohan; Kartiyani Harahap; Khairani Alawiyah Matondang; Noni Rozaini (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the role of individual ethics and organizational culture in maximizing organizational profitability. This study uses the library research method, where the study is based on the opinions of experts on individual ethics and organizational culture in maximizing company profitability. Individual ethics and organizational culture can be improved in quality to maximize company profitability. This can have an effect on a micro and macro scale by providing short and long term effects for all elements and the company's environment